Influence of transmucosal height in abutments of single and multiple implant-supported prostheses: a non-linear three-dimensional finite element analysis - Borie, Eduardo; Leal, Eduardo; Orsi, Lara Augusta; Salamanca, Carlos; Dias, Fernando José; Weber, Benjamin
The aim of this study was to analyze the influence of three different transmucosal heights of the abutments in single and multiple implant-supported prostheses through the finite element method. External hexagon implants, MicroUnit, and EsthetiCone abutments were scanned and placed in an edentulous maxillary model obtained from a tomography database. The simulations were divided into two groups: (1) one implant with 3.75 × 10 mm placed in the upper central incisor, simulating a single implant-supported fixed prosthesis with an EsthetiCone abutment; and (2) two implants with 3.75 × 10 mm placed in the upper lateral incisors with MicroUnit abutments, simulating a multiple implant-supported prosthesis. Subsequently, each group was subdivided into three models according to the transmucosal height (1, 2, and 3 mm). A static oblique load at an angle of 45 degrees to the long axis of the implant in palatal-buccal direction of 150 and 75 N was applied for multiple and single implant-supported prosthesis, respectively. The implants and abutments were assessed according to the equivalent Von Mises stress analyses while the bone and ceramics were analyzed through maximum and minimum principal stresses. The total deformation values increased in all models, while the transmucosal height was augmented. The transmucosal height of the abutments influences the stress values at the bone, ceramics, implants, and abutments of both the single and multiple implant-supported prostheses, with the transmucosal height of 1 mm showing the lowest stress values.